2017
DOI: 10.1002/cbdv.201700280
|View full text |Cite
|
Sign up to set email alerts
|

Variation on Composition and Bioactivity of Essential Oils of Four Common Curcuma Herbs

Abstract: Chemical compositions, antioxidative, antimicrobial, anti-inflammatory, and cytotoxic activities of essential oils extracted from four common Curcuma species (Curcuma longa, Curcuma phaeocaulis, Curcuma wenyujin, and Curcuma kwangsiensis) rhizomes in P. R. China are comparatively studied. In total, 47, 49, 35, and 30 compounds are identified in C. longa, C. phaeocaulis, C. wenyujin, and C. kwangsiensis essential oils by GC/MS, and their richest compounds are ar-turmerone (21.67%), elemenone (19.41%), curdione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 36 publications
(40 reference statements)
0
10
0
3
Order By: Relevance
“…All of these species contain at least 1 active ingredient from polysaccharides, flavonoids, or flavonoid glycosides . In vivo and in vitro studies have shown that these bioactive components may augment the immune response, enhance antioxidant abilities, induce apoptotic pathways, and suppress cancer cell migration . Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…All of these species contain at least 1 active ingredient from polysaccharides, flavonoids, or flavonoid glycosides . In vivo and in vitro studies have shown that these bioactive components may augment the immune response, enhance antioxidant abilities, induce apoptotic pathways, and suppress cancer cell migration . Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages .…”
Section: Discussionmentioning
confidence: 99%
“…This was later reinforced by Kikuchi et al, who adopted this pathway to rationalize the presence of a novel oxygenated isodaucene from C. zedoaria . The observation of isodaucenes from Curcuma plants is of particular interest within the context of this work, since these plants are also frequently found to contain zerumbone and zerumbone epoxides …”
Section: Results and Discussionmentioning
confidence: 99%
“…In our case, we used the direct exposure of O. gratissimum and C. nardus to S. cerevisiae cells. This cell type has been widely used for the evaluation of toxicity of substances, including assays with EOs (Zhang et al ., 2017; Armijos et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%